Fanfic'ing Film: Queer Youth Cinema Reclaims Pop Culture. Issue 1 (1st March 2019) - Scahill, Andrew
Abstract : Fairy Tales Film Festival 2018, Calgary Queer Arts Society, Youth Queer Media Program For the study of youth in cinema, we, as scholars, must always remind ourselves that most images we analyze are created by adults representing youth, not by youth representing themselves. As such, they represent an idea of youth—a memory, a trauma, a wish. They are stories these adults tell themselves about what they need youth to be in that moment. Coming out becomes the singular narrative of queer youth, and positions adulthood as a safe and stable destination after escaping the traumatic space of adolescence. The stories in these films provide important moments for adult queers to "feel backward" (2009: 7) as Heather Love says, and to process the pain of a queer childhood. And for young people exploring their sexuality, these stories are essential for at-risk youth who feel hopeless, trapped, or alone.